2022
DOI: 10.1111/jfpp.16818
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of ten newly isolated phages against the foodborne pathogen Shigella flexneri

Abstract: Ten bacteriophages with lytic activity against Shigella flexneri were tested for their resistance to physicochemical conditions found in food matrices. Phage viability and activity were evaluated at different temperatures, pH values, and NaCl concentrations.In addition, challenge tests with each individual phage against ATCC 12022 were conducted to evaluate their use as biocontrol agents. Although phages showed high resistance up to 60°C, Shi30, Shi33, and Shi93 showed higher thermal resistance (70°C).The ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Our previous results indicated that phage viability was not significantly affected from pH 5 to pH 11, yet, at pH 3, a significant reduction in viability was observed. In addition, the activity of the 10 phages tested in this work was the same at 5 < pH < 9 and was slightly affected at 3 < pH < 5 and 9 < pH < 11 [14]. As previously observed by others [8,20,28], our phages were highly stable in a wide range of pH values (Figure 4).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our previous results indicated that phage viability was not significantly affected from pH 5 to pH 11, yet, at pH 3, a significant reduction in viability was observed. In addition, the activity of the 10 phages tested in this work was the same at 5 < pH < 9 and was slightly affected at 3 < pH < 5 and 9 < pH < 11 [14]. As previously observed by others [8,20,28], our phages were highly stable in a wide range of pH values (Figure 4).…”
Section: Discussionsupporting
confidence: 86%
“…Prior to adsorption assays, viability of phages at refrigeration (4 • C), room (25 • C) and abusive (50 • C) temperatures was evaluated. All the phages tested showed a high resistance from 4 to 50 • C [14]. In agreement, two phages (vB_SflS-ISF001 and vB-SdyS-ISF003) active against S. flexneri [18] and S. dysenteriae [24], respectively, proved to have a high thermal stability in the range of -20 to 60 • C. Phages adsorbed efficiently at low (Shi3, Shi22, Shi30, Shi33, Shi34 and Shi88), at moderate (AShi, Shi34, Shi40, Shi93 and Shi113) and at high (AShi, Shi 22, Shi30 and Shi33) temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations